The effects of socio-economic status on the stress of University students - Raff, Mirriam (My University, 2016)
Previous international research suggests there is a relationship between socioeconomic status and stress levels at college, or University. The aim of this study was to determine whether students at the University of the Witwatersrand socio economic status affected their stress levels. The sample of thirty two students included both students from privileged backgrounds and those that were from underprivileged backgrounds, in varying degrees. The data was collected through paper based questionnaires over a ten week time period. The methodological standpoint with which the research wished to engage with the study was quantitative in nature and therefore the approach of the study and administration of instruments and data analysis were necessarily quantitative in nature. The relationship between the dependant (stress) and independent (Socio-economic status) variables were highlighted. The researcher chose to use a quantitative approach for the study given that the variables under investigation in the current study are believed to be manifest and as such utilised a questionnaire (Mueller & Hancock, 2010). The measuring of variables based on the questionnaire, in order to express the relationship between socio-economic status, and stress by using effect statistics such as correlations, relative frequencies, and differences between means in order to test the correlation between the two variables. In order to explore this relationship, a point biserial correlation was conducted and its respective assumptions were tested. Secondary questions explored whether differences existed between students with a job, versus those without a job, students from two parent families, and those who are not, and students who are the first to study in their families, and those who are not Furthermore, results of the questionnaires were quickly and easily quantified by the researcher which allowed the data to be analyzed more scientifically and objectively. The information from the survey gives the University of Witwatersrand a clearer understanding of the stress students experience based on their socio economic status. Key Words: Socioeconomic status, stress, students, relationship.
In partial fulfilment of the requirements For the degree Bachelor of Social Work